2021
DOI: 10.3390/pharmaceutics13081309
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Combined Rifampicin Formulations Delivered by the Pulmonary Route to Treat Tuberculosis in the Guinea Pig Model

Abstract: Liposomes, as vehicles alone or in combination with rifampicin (RIF) microparticles (RMs), were evaluated as vehicles to enhance the permeation of RIF into granulomas. RIF liposomes (RLs) were extruded through a 0.1 µm polypropylene membrane. RMs were prepared by the solvent evaporation method. Four weeks after infection, guinea pigs (GPs) were assigned to groups treated with a combination of RM-RLs or RLs alone. RLs were nebulized after extrusion whereas RMs were suspended in saline and nebulized to GPs in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…A comparison of each treatment was performed using a non-parametric ANOVA (Kruskal–Wallis test) with Dunnett’s multiple comparison test to determine which experimental groups were significantly different from each other. The p -values for the primary analysis and the adjusted p -values for the multiple comparisons <0.05 were considered statistically significant [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…A comparison of each treatment was performed using a non-parametric ANOVA (Kruskal–Wallis test) with Dunnett’s multiple comparison test to determine which experimental groups were significantly different from each other. The p -values for the primary analysis and the adjusted p -values for the multiple comparisons <0.05 were considered statistically significant [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…This enhancement indicates their potential as nanocarriers for poorly soluble anti-TB drugs. [ 257 ] RIF-loaded Liposomes 137 N/A In this study, the guinea pigs were exposed to an inhalation dose of 2.83 mg/kg Significant reduction in inflammation levels, inferred from the organ weights, and a decreased bacterial load in the lung regions of the guinea pigs, suggesting that the nanocarrier enhances granulomatous penetration [ 258 ] Hydrophilic Streptomycin Sulfate SLNs (STRS-SLN) 218.1 Enhanced intracellular absorption in THP-1, LoVo, and DLD-1 cells. 3-fold MIC reduction against MTB H37RV compared to free STRS Wistar rats, oral administration 90 mg/kg STRS-SLN plasma concentration surpassed the STRS group.…”
Section: Nanoscale Drug Delivery Systemsmentioning
confidence: 99%
“…García-Contreras et al [ 285 ] developed two systems: RIF-loaded liposomes (comprising L-α-phosphatidylcholine and cholesterol) and RIF-loaded PLGA microparticles (by the emulsion/solvent evaporation method). They individually assessed the penetration capabilities of both nanosystems into granulomas.…”
Section: Nanoscale Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary TB is the most common form of TB, and inhalable carriers of ATDs have been a major focus of research and were found to significantly increase targeting in the lungs, reducing undesirable toxic side effects and enabling delivery to AM [9,14]. Liposomes [261], microparticles [186,187,262], microencapsulation [80], liquid crystals [263], hydrogels [244], polymeric micelles [96] and even hybrid systems [264] have been promising for inhalational TB therapy. The formulations need to be optimized to penetrate mucous layers and biofilms and overcome sequestration, rapid deactivation by enzymes, and elimination by coughing [265,266].…”
Section: Targeted Therapymentioning
confidence: 99%